What does 'Coming to the Aid of Logos' mean? Structure and Aim of thePlatonic Dialogues - Szlezák, Thomas (2000)
The central concept of the critique of writing (Phaedrus274b278e). Many passages of the dialogues themselves show what this means: not a justification of the first lagos by means of additional arguments on the same level (as Vlastos ascertains), but a deliberate recourse to higher-leveled arguments that may bring us closer to the ápxfÍ.That the Platonic philosopher be always capable of coming to the aid of the written lagos orally, thus revealing it as inferior (278bc), implies that he does not express all of his philosophy in writing, but that he guards what is "more valuable" (his Hf.Lt<:nepcx) for speech.